2006
DOI: 10.1093/intqhc/mzl009
|View full text |Cite
|
Sign up to set email alerts
|

The influence of observation and setting on community health workers’ practices

Abstract: We found that community health workers made treatment errors less frequently when they were observed in a hospital in-patient or outpatient department than when they were not observed in the community. Evaluations that involve the observation of community health workers in a hospital setting might overestimate the quality of care that they normally give in their villages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 12 publications
3
35
0
Order By: Relevance
“…The Hawthorne Effect is an acknowledged limitation of non-participant structured observation, the key method used in this study [22], [23], [24]. Health workers who are conscious of the fact they were being observed may have altered their behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…The Hawthorne Effect is an acknowledged limitation of non-participant structured observation, the key method used in this study [22], [23], [24]. Health workers who are conscious of the fact they were being observed may have altered their behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Previous examinations of the quality of care delivered through CCM have evaluated pilot programmes in limited geographic areas (Kelly et al 2001; Rowe et al 2007a), or have assessed the skills of CCM providers, rather than quality of services received by sick children, through tests of knowledge (Zeitz et al 1993; Ashwell and Freeman 1995), reviews of case registers (Mehnaz et al 1997; Rowe et al 2006; Rowe et al 2007b) or through role plays and case scenarios (Zeitz et al 1993; Kallander et al 2006). Previous observation-based studies of sick child care have evaluated care for a single disease or have observed CCM providers at health facilities rather than their normal practice settings (Zeitz et al 1993; Ashwell and Freeman 1995; Kelly et al 2001; Hadi 2003; Rowe et al 2006; Rowe et al 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…Previous observation-based studies of sick child care have evaluated care for a single disease or have observed CCM providers at health facilities rather than their normal practice settings (Zeitz et al 1993; Ashwell and Freeman 1995; Kelly et al 2001; Hadi 2003; Rowe et al 2006; Rowe et al 2007a). This study uses rigorous, community-based observation methods with ‘gold-standard’ clinical reassessments to evaluate the quality of care for sick children in the context of a CCM programme being implemented at scale.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that both health workers and carers of children may have changed their behaviours because they were being observed. Such Hawthorne effects are well documented [17,18]. It was assumed that the behaviours observed here were ‘best behaviours’ of both the health workers and the carers.…”
Section: Discussionmentioning
confidence: 58%